The Dynamics and Challenges of Election and Democratic Consolidation in Nigeria: A Study of 2019 and 2023 Gubernatorial Election in Kano State - Abdulrasheed Abdulyakeen; Haruna Adamu Aliero (Acta Politica Polonica)
This study examines the Elections and Democratic Consolidation in Nigeria: A Study of 2019 And 2023 Gubernatorial Election in Kano State. Multi-stage cluster sampling procedure was used in sampling population for this study. First, clusters of local governments in each of the selected states were randomly selected. Secondly, clusters of political wards in each of the selected Local Government Areas were randomly selected. A total of four hundred questionnaires were distributed across all the selected areas to elicit information on the subject matter but three hundred and eighty four were retrieved. Findings revealed most voters are induced with money by politicians both those in power and those seeking to be in power to influence voters‟ choice of candidate or political party in order to retain or capture political power during elections, during 2019 and 2023 general elections. Findings also revealed that the level of voters turn out during presidential and national assembly elections is higher than during gubernatorial and state assembly elections which poses a challenge to democracy at grass root and the degree of rigging, malpractices and irregularities was higher in presidential and national assembly elections than in gubernatorial and state assembly elections. Away out of this